A genetic and virulence characterization of Brazilian strains of Mycoplasma hyopneumoniae - Toledo, Leonardo Teófilo; de Souza, Luiz Fernando Lino; Pereira, Carlos Eduardo Real; Polveiro, Richard Costa; Bressan, Gustavo Costa; Yamatogi, Ricardo Seiti; Jeong, Kwangcheol Casey; Marks, Fernanda Simone; Diamantino, Caio Augustus; de Carvalho, Victor Hugo Rabelo; Malcher, Clarisse Sena; Petri, Fernando Antônio Moreira; et al. (Frontiers in Microbiology, 2023)
Mycoplasma hyopneumoniae (M. hyopneumoniae) is considered the primary causative agent of porcine enzootic pneumonia (EP), a chronic contagious respiratory disease that causes economic losses. Obtaining new pathogenic isolates and studying the genome and virulence factors are necessary. This study performed a complete sequencing analysis of two Brazilian strains, UFV01 and UFV02, aiming to characterize the isolates in terms of the virulence factors and sequence type. The complete genome analysis revealed the main virulence genes (mhp385, mhp271, MHP_RS03455, p102, p97, p216, MHP_RS00555, mhp107) and ST-123, the presence of three toxin-related genes (tlyC, PLDc_2 and hcnC), and some genetic groups specific to these two isolates. Subsequently, the pathogenicity of the isolates was evaluated via an experimental infection conducted in a swine model. The study was divided into three groups, namely a negative control group (n = 4) and two test groups (n = 8), totaling 20 animals. They were challenged at 35 days of age with 107 CCU (Color Changing Units) M. hyopneumoniae via the intratracheal route. The UFV01 group showed earlier and higher seroconversion (IgG) (100%), while only 50% of the UFV02 group seroconverted. The same trend was observed when analyzing the presence of IgA in the bronchoalveolar lavage fluid (BALF) at 35 days post-infection (dpi). The UFV01 group had a mean macroscopic lesion score of 11.75% at 35 dpi, while UFV02 had 3.125%. Microscopic lesions were more severe in the UFV01 group. Based on laryngeal swab samples evaluated by qPCR, and the detection began at 14 days. The UFV01 group showed 75% positivity at 14 dpi. The UFV02 group also started excreting at 14 dpi, with a positivity rate of 37.5%. The results indicate that the UFV01 isolate exhibits higher virulence than UFV02. These findings may aid in developing new vaccines and diagnostic kits and establishing experimental models for testing.